An Analytical Study on the Violence Against Children During Covid-19 Period in Bangladesh - Md. Abu Shahen (CV. Literasi Indonesia, 2022)
This paper tried to know the different forms of violence against children during the Corona pandemic in Bangladesh from 2020 to mid-2021. As we have already experienced this catastrophic and lives losing pandemic situation across the world wherein the people of Bangladesh have been uniquely facing this live losing situation since 2020. World Health Organization has warned people to adopt different precautionary measures like 20-second hand washing, wearing a mask, maintaining physical and social distance, isolation, quarantine, taking immediate treatment, and vaccination. The real situation is that many countries have failed to take these measures and lost a huge number of lives. In spite of those situations, many developed countries have taken precautionary measures to prevent mass transmission of the Covid-19 virus. But unfortunately, many socio-economic problems like violence against children and women have been aroused during this pandemic situation while governments have given more concentration on Covid-19 prevention, e.g., isolation, quarantine, awareness of social measures, and vaccination. However, this paper found that various types of violence have increased during this pandemic situation, such as domestic violence against children, movement of the children, and domestic corporal violence. Moreover, this paper found weaknesses in the existing legal protections for children to prevent violence against children.